Diagnosis and management of skeletal fluorosis in current scenario: a case report - Jain, Jalaz; Dudeja, Shankey; Nandal, Gaurav; Sihag, Ravi; Kumar, Vibhuti; Jain, Deepika (International Journal of Research in Orthopaedics, 2020)
Skeletal fluorosis is a rare form of toxic metabolic disease of bone characterised by increased incorporation of fluoride in bone. Skeletal fluorosis generally occurs in endemic regions where there is increased ingestion of fluorine in water and or food over a long period of time. Fluorosis is a spectrum of disease ranging from dental, non-skeletal fluorosis to skeletal fluorosis. The disease is characterised by typical clinical and radiological features that raise the suspicion towards diagnosis of the disease. Radiographic features are characterized by generalised osteosclerosis and later ossification of ligaments, tendons and interosseous membranes. Skeletal fluorosis can be easily confused with other rheumatologic disorders. People exposed to large amounts of fluoride show dental changes much earlier than the skeletal effects. Management of fluorosis generally focuses on symptomatic treatment.